Pengembangan Media Petarung Berbasis Multimedia Berbantuan Lagu untuk Meningkatkan Hasil Belajar IPAS Materi Rantai Makanan Kelas V Sekolah Dasar - Fadhilah, Rima; Sutikno, Putri Yanuarita (Universitas Muhammadiyah Magelang, 2026)
This study aims to develop the Petarung (Food Chain Adventure) multimedia-based learning media assisted by songs and to determine its feasibility and effectiveness in improving students’ learning outcomes in IPAS on the topic of food chains for fifth-grade students at SDN 01 Kepatihan. This research employed a Research and Development (R&D) method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected through interviews, observations, needs questionnaires, expert validation sheets, response questionnaires, and pretest–posttest assessments. Data analysis was conducted using descriptive quantitative and qualitative techniques, supported by the Shapiro–Wilk normality test, Paired Sample t-Test, and N-Gain test to measure effectiveness. The results showed that the developed media obtained an average validation score of 87.29%, categorized as very feasible. The t-test result indicated a significance value of 0.001 (Sig. < 0.05), demonstrating a significant improvement in learning outcomes. The N-Gain score in the small group was 0.8026 and in the large group was 0.7718, both categorized as high. Therefore, the Petarung multimedia-based learning media assisted by songs is highly feasible and effective in improving students’ learning outcomes in IPAS on the topic of food chains in elementary school.